2017
DOI: 10.1002/jcad.12146
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress Disorder and Emotion-Focused Coping Among Disaster Mental Health Counselors

Abstract: The authors surveyed 235 disaster mental health counselors (DMHCs) for levels of posttraumatic stress disorder (PTSD) symptom severity. A correlational design was used to examine the roles of adult attachment security, emotion regulation, and mindfulness in predicting PTSD symptoms among this group. Each of the 3 predictors was negatively correlated with PTSD symptom severity, and data supported a mediating role for emotion regulation. Results may inform DMHCs, other counselors, and individuals who train or de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 48 publications
2
9
0
Order By: Relevance
“…Moreover, we need to better identify personal and organization‐based strategies that could protect or exacerbate the vulnerability of MHW in case of another social crisis. As such, emotional regulation abilities, psychological flexibility, and coping strategies have been stressed as significant protective factors against MHW's distress in past studies (Biron & Van Veldhoven, 2012 ; Cengil, 2019 ; Collins, 2008 ; Pow & Cashwell, 2017 ; Rodriguez & Carlotto, 2017 ). We also know that low job and salary satisfaction and the use of passive coping strategies predict greater emotional exhaustion among child protection workers and in‐home caregivers (Jenaro et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we need to better identify personal and organization‐based strategies that could protect or exacerbate the vulnerability of MHW in case of another social crisis. As such, emotional regulation abilities, psychological flexibility, and coping strategies have been stressed as significant protective factors against MHW's distress in past studies (Biron & Van Veldhoven, 2012 ; Cengil, 2019 ; Collins, 2008 ; Pow & Cashwell, 2017 ; Rodriguez & Carlotto, 2017 ). We also know that low job and salary satisfaction and the use of passive coping strategies predict greater emotional exhaustion among child protection workers and in‐home caregivers (Jenaro et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Adult attachment styles are internal working models that frame expectations about intimate and romantic relationships (Collins et al, 2006) and may influence psychological well-being during times of traumatic stress such as COVID-19 (Moccia et al, 2020;Pietromonaco & Overall, 2020), terrorist attacks (Fraley et al, 2006), and natural disasters (Sandberg et al, 2010). Preparing counselors to provide disaster mental health services has been identified as an important area of training and research Pow & Cashwell, 2017), and has been found to impact the well-being of helping professionals . Disaster mental health counseling helps clients return to their baseline level of functioning while establishing safety and security (Sandoval et al, 2009).…”
mentioning
confidence: 99%
“…Researchers have examined the relationship between cognitive and emotional phenomena, social functions of emotions, mood, and ER with clients (D'Agostino, Covanti, Rossi Monti, & Starcevic, 2017; Gross, 2015; Hofmann, 2014; Linehan, 2015; Phelps, 2006). Additionally, scholars have focused on four areas of research with counselors and CITs: (a) emotional intelligence (Easton, Martin, & Wilson, 2008; Gutierrez, Mullen, & Fox, 2017; Olry‐Louis, 2018), (b) affective experiences (Melton et al, 2005), (c) emotional awareness (Skovholt & R⊘nnestad, 2003; Tangen, 2017), and (d) emotion‐focused coping (Pow & Cashwell, 2017). However, researchers have not focused on the integration of ER development within the counselor training process.…”
Section: Er Knowledge and Practicementioning
confidence: 99%